THE RELATIONSHIP BETWEEN HIGH PERFORMANCE WORK SYSTEM AND TURNOVER INTENTION: A GENERATION GAP STUDY - Ismail, Asrul Effendy bin; Bahron, Arsiah Haji (Malaysian Journal of Business and Economics (MJBE), 2020)
This research examines the relationship between factors of high-performance work systems (HPWS), which is element flexibility of HPWS among high skill contractor sector firm employees in Sabah. This is important in examining the effectiveness of human resource management practices in facilitating employee to sustain in the organization. The results showed that element flexibility of HPWS has the significant relationship with the turnover intention. In addition, the study also attempts to determine the differences in the turnover intention based on demographic study, which is generation gap or variables (age). The study also hypothesized that there are significant differences in the turnover intention of private-sector employees in the states of Sabah, Malaysia at different age and length of service and there is a dominant factor influencing turnover intention among employees in the construction organization. Questionnaire method has been used as a research instrument to obtain the data. A total of 107 respondents were randomly selected as a sample of study. The data was analyzed used "Statistical Package for Social Science" (SPSS Window) Version 12.0 as well as Smart PLS. The result of element flexibility of HPWS and turnover intention generally support the hypothesis. These findings show that this element HPWS factor should have given attention to retain employees in the organization. Some suggestions have been recommended for the contractor sector organizations and for future research to be completer and more comprehensive.